RANCANG BANGUN BELT CONVEYOR SEBAGAI ALAT MATERIAL HANDLING PENGANGKUT PASIR PADA PEMBUATAN BATA RINGAN - Aris Fiatno (Jurnal Teknik Industri Terintegrasi, 2021)
Abstract Conveyor in general is a tool that functions to move objects or loads from one place to another. In general, a belt conveyor system consists of a belt (belt), a front pulley (head pulley) equipped with a drive unit consisting of an electric motor and gearbox, a rear pulley (tail pulley), an upper idler (carry idler), and a lower idler. (return idlers). The method used in this research is the method of literature study and field observation. This research will also plan a design that is adapted to the conditions of the layout of the facility and also design according to the height of the mixer machine. Stages of data processing, the data processing process is carried out by finding the carrying capacity of the data processing process is carried out by calculating the speed of each series of conveyor belts using a time measuring device. the results of the design and manufacture of the belt conveyor that have been carried out, that the belt conveyor has a length of 4.5 m, with a frame width of 50, a height of 210 cm, using an electric motor with a power of hp. The conveyor belt that is made is capable of carrying a load of 4.3 tons per hour. Keywords: : Belt conveyor, material handling, hebel